Conventional synthetic disease-modifying antirheumatic drugs (csDMARD) in rheumatoid arthritis during pregnancy and lactation: a review - Pulungan, Yulianasari; Saputra, Andy Kurniawan; Purnamasari, Desy; Wijayanti, Nunuk; Sari, Laras Ratna (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2022)
Rheumatoid arthritis (RA) is an autoimmune and prominent inflammatory disorder that can affect wide of variety body systems, mainly joints. In Indonesia, the prevalence of RA is about 7.3% and mostly are women. The majority of women with RA are at childbearing and can be worsening throughout pregnancy and lactation. Conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) are the most common used medicine in RA for pregnancy and lactation. This scoping review was conducted using publications obtained from PubMed, Embase, The Cochrane Library, POPLINE, and Google Scholar concerning the safety of csDMARD in rheumatoid arthritis during pregnancy and lactation from 2011 to 2021. Among csDMARDs reviewed, sulfasalazine, hydroxychloroquine, chloroquine, and cyclosporine are relatively safe for pregnant and lactating women. However, they should be used in caution by considering the risk and benefit as well as under clinical supervision.